Heterogeneous Ice Nucleation by Soufriere Hills Volcanic Ash Immersed in Water Droplets - Mangan, T. P. (PLoS One, 2017)
Fine particles of ash emitted during volcanic eruptions may sporadically influence cloud properties on a regional or global scale as well as influencing the dynamics of volcanic clouds and the subsequent dispersion of volcanic aerosol and gases. It has been shown that volcanic ash can trigger ice nucleation, but ash from relatively few volcanoes has been studied for its ice nucleating ability. In this study we quantify the efficiency with which ash from the Soufriere Hills volcano on Montserrat nucleates ice when immersed in supercooled water droplets. Using an ash sample from the 11(th) February 2010 eruption, we report ice nucleating efficiencies from 246 to 265 K. This wide range of temperatures was achieved using two separate droplet freezing instruments, one employing nanolitre droplets, the other using microlitre droplets. Soufriere Hills volcanic ash was significantly more efficient than all other ash samples that have been previously examined. At present the reasons for these differences are not understood, but may be related to mineralogy, amorphous content and surface chemistry.